Strategi Komunikasi dalam Pemasaran Produk Home Industri di Kota Cirebon - Rozaq, Mahfudz (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Home industries represent a significant form of Micro, Small, and Medium Enterprises (MSMEs) that contribute to local economies. In Cirebon City, home industries producing snacks, batik, and handicrafts dominate the sector, creating employment and fostering the creative economy. However, limited capital, technology, and access to information create challenges in product marketing. This study aims to analyze communication strategies in marketing home industry products in Cirebon City and evaluate the effectiveness of communication media used. A mixed-method approach was employed, distributing questionnaires to 60 consumers and conducting in-depth interviews with 5 home industry actors. Findings reveal that 58% of consumers learn about products through word of mouth, 30% through social media (Instagram, WhatsApp, Facebook), and 12% through local fairs or exhibitions. Major obstacles include limited knowledge of digital marketing (75%), insufficient promotional capital (68%), and inconsistent branding (62%). While simple, relationship-based communication strategies remain dominant, digital media utilization is steadily increasing. The study recommends digital marketing training, brand identity strengthening, and the application of Integrated Marketing Communication (IMC) strategies to enable Cirebon’s home industries to expand market reach and enhance competitiveness.